Retaining graduates: research on the relationship among trust, organisational commitment, and graduate retention - Zheng, Qiulin (2019)
The retention of graduates in the company is becoming more and more essential for companies’ continuous development, because graduates are too talented to be ignored. In order to enhance graduate retention, this study would identify the link between institutional trust, trust in supervisors, trust in co-workers, organisational commitment and graduate retention organisations, trying to implement strategies of trust and organisational commitment that might improve the retention rate in the company.